ESTIMATION OF RADIOANXIETY OF MEDICAL HIGHER EDUCATIONAL INSTITUTIONS GRADUATES - T. B. Baltrukova; T. B. Djakonova-Djachenkova (Радиационная гигиена, 2015)
The article is devoted to an estimation of the level of radioanxiety of graduates of medical higher educational institutions and degree of their knowledge of negative influence of ionizing irradiation on the personnel and patients is considered. As their future trade directly or indirect – through patients, is connected with ionizing irradiation sources.